Treatment of effluent from a water and oil separator box: potential of reuse of effluent in a gas station (Research, Society and Development, 2021)
Gas station activities generally have the greatest potential to cause damage to the environment by chemicals, gases, solvents, metals and fuels in particular. The packaging of fuels in underground ditches is what most causes soil contamination. This study aims to analyze an effluent treatment structure from a water separator box and petrochemical by-products from a gas station, compare the results with the legislation and evaluate its potential for reuse in the process. In Brazil, the legislation pertaining to the fuel storage and distribution activity dates from 1997, with the edition of the Resolution of the National Environment Council (CONAMA) nº. 237/97, ​​which cites the activity as being requested for environmental licensing and CONAMA 430/2011 complements and amends Resolution No. 357/2005, which provides for the conditions and standards for the discharge of effluents. In the effluent leaving the separator box, we note that anomalies still occur, such as the excess of surfactants and also in the BOD, taking into account that these two parameters affect the water quality for its potential reuse, and may cause contamination in the soil and sheet. phreatic. We advise the use of the activated carbon filter, as it is a more viable method and can meet the need to return this effluent within standardized standards, allowing the reuse of effluent in discharges, gardening, washing environments, among others.